Can China's resource-saving and environmentally friendly society really improve the efficiency of industrial land use? - Wenfang Pu; Anlu Zhang; Lanjiao Wen (Land, 2021)
The Chinese government is committed to its goal of building a resource-saving and environmentally friendly society (RES). The hope is that establishing an RES will accelerate social and economic development, improve resource utilization, and transform industrialization. This paper focuses on the Changsha–Zhuzhou–Xiangtan urban agglomeration (CZTUA) in Hunan Province, which is a pilot for the RES, as an example. A slack-based measure model based on data envelopment analysis was used to evaluate industrial land use efficiency (ILUE), which includes undesirable outputs. We collected panel data from 2003 to 2018 and used the difference-in-differences method to investigate whether the ILUE in the CZTUA has improved since the implementation of the RES in 2007. The results showed that: (1) the ILUE in the CZTUA increased from 0.25 in 2003 to 0.48 in 2018; (2) from 2007 to 2018, the establishment of the RES increased the ILUE in the CZTUA by 24.6%; (3) gross domestic product and the secondary industry structure ratio had key roles in improving the ILUE in the CZTUA; (4) there is an inverted U-shaped relationship between economic development and the ILUE in the CZTUA; (5) since the establishment of the RES, the pollution emission index of the CZTUA has clearly decreased each year. These findings not only provide a reference for the Chinese government for following up the formation of the RES and its promotion in other regions of China, but may also contribute to sustainable economic development in other transitional countries in the world.
Keywords: 330; resource saving and environmentally friendly society (RES); industrial land use efficiency (ILUE); SBM model; desirable and undesirable outputs; difference-in-differences method (DID); Changsha-Zhuzhou-Xiangtan urban agglomeration (CZTUA); sustainable development